Environmental friendly irrigation of vegetables with high salt content water - Zsembeli, József; Szűcs, Lilla (Acta Agraria Debreceniensis, 2014)
Horticultural activities have been characteristic in the hobby gardens located in the northern and western areas around the town of Karcag for more than 300 years. During the droughty summer periods, characteristic to the region, the water demand of vegetables and fruit trees are covered by irrigation, for that the water is gained from drilled wells. These well waters contain high amount of dissolved salts contributing to the secondary salinization of the soil. Taking these facts into consideration an irrigation experiment was set at the lysimeter station of Karcag Research Institute. Our goal was to mitigate the risk of secondary salinization generated by irrigation with waters of high salt content and to survey the application possibilities of soil preserving irrigation.